2016
DOI: 10.1080/14656566.2016.1202923
|View full text |Cite
|
Sign up to set email alerts
|

New treatments on the horizon for chemoradiotherapy-induced nausea and vomiting

Abstract: Antiemetic prophylaxis for patients receiving concomitant chemoradiotherapy has, for many years, been an orphan research area. The distinction between acute and delayed nausea and vomiting does not apply to fractionated radiotherapy, and prophylaxis should be considered to cover the entire course of treatment and not only the acute and delayed chemotherapy-induced nausea and vomiting. The best prophylaxis in women receiving fractionated radiotherapy and concomitant weekly cisplatin is a combination of the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Chinese herbal therapy typically takes advantage of natural substances that are less toxic and have fewer side effects compared to chemoradiotherapy drugs ( 11 ). Chemoradiotherapy can cause side effects such as nausea, vomiting, hair loss, and fatigue, whereas Chinese herbal therapy is generally well-tolerated and can improve quality of life ( 12 , 13 ). Chinese herbal therapy is tailored to the individual patient’s needs and can be adjusted based on their response to treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese herbal therapy typically takes advantage of natural substances that are less toxic and have fewer side effects compared to chemoradiotherapy drugs ( 11 ). Chemoradiotherapy can cause side effects such as nausea, vomiting, hair loss, and fatigue, whereas Chinese herbal therapy is generally well-tolerated and can improve quality of life ( 12 , 13 ). Chinese herbal therapy is tailored to the individual patient’s needs and can be adjusted based on their response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoradiotherapy can weaken the immune system, making the patient more vulnerable to infections and other complications ( 14 , 15 ). Overall, while there is still much to learn about the potential of TCM for the treatment of tumor, research to date suggests that it may have a role to play in improving outcomes for cancer patients ( 12 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study demonstrated that one third of patients experiencing RINV would like additional treatment [ 5 ]. Nevertheless, evidence for the guideline recommendations is scarce, and little is known about the combination and optimal duration of antiemetic agents [ 6 ]. In the chemoradiotherapy setting, RINV can be exacerbated by concomitant chemotherapy to higher levels, which has been confirmed by prior studies, though the pathophysiological mechanism is not well understood [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%